2023
DOI: 10.1021/acsami.2c20070
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Analysis of Organic Light-Emitting Diodes through Dispersive Magneto-Electroluminescence Response

Abstract: Understanding the stability and degradation of organic light-emitting diodes (OLEDs) under working conditions is a significant area of research for developing more effective OLEDs and further improving their performance. However, studies of degradation processes by in situ noninvasive methods have not been adequately developed. In this work, tris-(8-hydroxyquinolino) aluminum (Alq3)-based OLED degradation processes have been analyzed through the investigation of the device dispersive magneto-electroluminescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This trend is maintained at a higher voltage of 5 V. According to the Merrifield theory, this trend is completely different from that of TTF-based devices, which display a weakened MEL signal at the high-magnetic-field region (50–250 mT). Furthermore, the magnetic field indicating half of saturated MEL intensity (B 0 ) was ∼18.2 mT, which is over the conventional B 0 region showing a sharp increase by hyperfine field interaction (HFI) between 4 and 10 mT . This suggests the presence of a mechanism that is more dominant than HFI.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This trend is maintained at a higher voltage of 5 V. According to the Merrifield theory, this trend is completely different from that of TTF-based devices, which display a weakened MEL signal at the high-magnetic-field region (50–250 mT). Furthermore, the magnetic field indicating half of saturated MEL intensity (B 0 ) was ∼18.2 mT, which is over the conventional B 0 region showing a sharp increase by hyperfine field interaction (HFI) between 4 and 10 mT . This suggests the presence of a mechanism that is more dominant than HFI.…”
Section: Resultsmentioning
confidence: 89%
“…Furthermore, the magnetic field indicating half of saturated MEL intensity (B 0 ) was ∼18.2 mT, which is over the conventional B 0 region showing a sharp increase by hyperfine field interaction (HFI) between 4 and 10 mT. 31 This suggests the presence of a mechanism that is more dominant than HFI.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…When a device fails, it is usually due to electrical short circuits, the most severe type of failure. These shorts occur due to imperfections on the surface of the device's substrate, such as particles, rough surfaces, or local heating during operation [45][46][47][48]. The heat generated by these imperfections can also cause structural changes in the device, potentially leading to electrode contact or damage to the cathode material [49][50][51].…”
Section: Catastrophic Failurementioning
confidence: 99%
“…Wang et al categorized the decay stages into three categories to better understand the decay behavior [79]. Additionally, Aziz et al identified dark-spot degradation, catastrophic failure, and intrinsic deterioration as the main causes of OLED luminance loss [48]. Ishii et al explained that luminance decay occurs in two phases, exponential decay due to chemical degradation and a quick downward movement due to an internal electric field [80].…”
Section: Luminance Decaymentioning
confidence: 99%